2022
DOI: 10.4102/sajems.v25i1.4460
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing blockchain adoption in the South African clearing and settlement industry

Abstract: New technologies create opportunities to enhance and revolutionise current processes (Greco 2019). In 1997, STRATE was introduced; this system allowed for the replacement of paper Background: The adoption of and improvements in new technology in the South African capital market historically led to increased trade capacity and liquidity, which may be linked to the growth in market size.Aim: In this study the aim is to investigate factors that will influence the adoption of blockchain technology in the South Afr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…Any mature securities market must have a securities settlement system with a sound legal system, complete functions, safe operation, and advanced technology. In such a securities registration and settlement system involving numerous investors, it is crucial to enhance its security and efficiency (Baiod et al, 2021;Etemadi et al, 2021;Levis et al, 2021;Dowelani et al, 2022). Only by ensuring their trust can they actively participate in trading.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Any mature securities market must have a securities settlement system with a sound legal system, complete functions, safe operation, and advanced technology. In such a securities registration and settlement system involving numerous investors, it is crucial to enhance its security and efficiency (Baiod et al, 2021;Etemadi et al, 2021;Levis et al, 2021;Dowelani et al, 2022). Only by ensuring their trust can they actively participate in trading.…”
Section: Introductionmentioning
confidence: 99%
“…Third, blockchain technology can significantly reduce costs associated with securities settlement by eliminating intermediaries and minimizing manual processes. This eliminates the need for maintaining separate records and performing reconciliations, resulting in cost savings for market participants (Baiod et al, 2021;Etemadi et al, 2021;Levis et al, 2021;Trivedi et al, 2021;Dowelani et al, 2022;Mushaddik et al, 2023). Additionally, blockchain can increase accessibility by enabling fractional ownership and facilitating the trading of securities in smaller denominations, opening up investment opportunities for smaller investors and institutions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The additional benefit of adopting blockchain technology is referred to as the relative advantage, and it is measured in comparison to the required expenses of converting to blockchain technology. Dowelani et al (2022) identified "people, organizations, technology, and industry" as significant elements that are likely to significantly impact the implementation of blockchain technology in South Africa. They were able to accomplish this by conducting data collection among "stakeholders in the clearing and settlement cycle/process of securities" in the South African capital market using interviews that were only partially structured.…”
Section: Conditions For Blockchain Adoption In African Bureaucracymentioning
confidence: 99%
“…They identified which aspects of the blockchain technology adoption landscape in South Africa are most significant. Conventional frameworks for blockchain technology adoption in the South African settlement and clearing industry were expanded and contributed to by Dowelani et al (2022), who added five new factors to the mix, including "trust, load shedding, unemployment/layoffs, current infrastructure, useful life, and educational campaigns." When analyzing the literature and findings of various scholars, the factors influencing the adoption of blockchain technology can be summarized as shown in Figure 4.…”
Section: Conditions For Blockchain Adoption In African Bureaucracymentioning
confidence: 99%